OA32 UK Paediatric Rheumatology Clinical Studies Group research priorities - results of a multidisciplinary consultation and consensus exercise. (23rd April 2022) - Smith, Eve M. D; Egbivwie, Naomi; Cowan, Katherine; Ramanan, Athimalaipet V; Pain, Clare E
Abstract: Background/Aims: The evidence base underlying the management of children and young people (CYP) with paediatric rheumatic diseases (PRDs) is inadequate, with many critical outstanding questions warranting investigation. The aim of this study was to elicit multidisciplinary PRDs research priorities, through consultation with patients, carers and healthcare professionals. Methods: This study was led by the UK NIHR CRN Children/Versus Arthritis Paediatric Rheumatology CSG (referred to as 'the CSG') and its Topic Specific Groups (TSGs). The CSG is a multidisciplinary group with strong patient/parent representation, supporting the development of clinical studies in the UK. Research priority ideas were sought from paediatric rheumatologists, trainees, allied healthcare professional (AHP), nurses, patients, parents and charities, through online surveys and face-to-face meetings. Research ideas were categorised as disease-specific or broad/general. They were grouped into sub-themes, duplicates/questions that had already been answered were removed, and similar submissions combined. A modified Delphi process was undertaken, including online research priority ranking, and an online consensus workshop to derive top PRD research priorities. Results: The initial consultation yielded 304 research priority ideas; 25% from patients/parents, 22% from the CSG, 18% from TSGs, 13% from AHPs, 11% from trainees, 11% from Nurses. 55 disease-specific and 37 broad/general research priorities were voted upon in the first online survey, yielding a top 11 general broad research priorities. The top 10 disease specific priorities were discussed at the online Delphi priority setting workshop, and two online surveys were held during the workshop to determine their final ranking. Two of the disease-specific priorities were combined, leading to a top 9 (see Table). Disease specific proprieties related to clinical trials in JIA (n = 3) / Juvenile Dermatomyositis (n = 1) / Chronic Recurrent Multifocal Osteomyelitis (n = 1) / Juvenile Systemic Lupus Erythematosus (n = 1) Scleroderma (n = 1), management of JIA in adulthood (n = 1) and chronic pain (n = 1). Conclusion: UK consensus-based PRD research priorities have been derived, underpinned by collaboration with patients/carers and healthcare professionals, helping to guide funding bodies to improve the evidence base in PRD's. Disclosure: E.M.D. Smith: None. N. Egbivwie: None. K. Cowan: None. A.V. Ramanan: None. C.E. Pain: None.